2022
DOI: 10.1186/s13098-022-00937-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma-derived extracellular vesicles on angiogenesis and the ensuing proliferative diabetic retinopathy through a miR-30b-dependent mechanism

Abstract: Background/purpose Proliferative diabetic retinopathy (PDR) is a major diabetic microvascular complication, characterized by pathological angiogenesis. This study sets out to investigate the potential molecular mechanism in the angiogenesis during PDR. Methods The expression of microRNA-30b (miR-30b) was quantified in a streptozotocin (STZ)-induced mouse model of PDR. The binding affinity between SIRT1 and miR-30b was then identified and validated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Another study explored the impact of plasma-derived EVs on angiogenesis and the progression of proliferative diabetic retinopathy (PDR), with a focus on the role of microRNA-30b. This research suggests that the mechanisms influenced by plasma-derived EVs may regulate angiogenesis in PDR via a mechanism dependent on miR-30b [ 150 ].…”
Section: Cts-evs In Physiology and Pathologymentioning
confidence: 99%
“…Another study explored the impact of plasma-derived EVs on angiogenesis and the progression of proliferative diabetic retinopathy (PDR), with a focus on the role of microRNA-30b. This research suggests that the mechanisms influenced by plasma-derived EVs may regulate angiogenesis in PDR via a mechanism dependent on miR-30b [ 150 ].…”
Section: Cts-evs In Physiology and Pathologymentioning
confidence: 99%
“…This transfer activates S1P1/AKT/VEGFR2 pathway, exacerbating abnormal angiogenesis 59 . Additionally, the increased tumor necrosis factor-α-induced protein 8 (TNFAIP8) and miR-30b in plasma EVs have been revealed to promote proliferation in human retinal microvascular endothelial cells 60 , 61 , making them crucial mediators of angiogenesis. Recent research has also discovered low levels of lncRNA PPT2-EGFL8 and elevated miR-423-5p in plasma EVs derived from PDR patients.…”
Section: Evs In Dr Pathology and Diagnosismentioning
confidence: 99%
“…Wang et al [ 157 ] also found that miR-30b was upregulated and SIRT1 was downregulated in the retina of diabetic mice, indicating a regulatory relationship between miR-30b and SIRT1. Inhibiting miR-30b led to an increase in SIRT1 expression, thereby reducing angiogenesis in retinal microvascular endothelial cells.…”
Section: Micrornas Participate In Dr Development By Different Mechanismsmentioning
confidence: 99%